2017
DOI: 10.1080/21541264.2017.1291395
|View full text |Cite
|
Sign up to set email alerts
|

Two possible modes of pioneering associated with combinations of H2A.Z and p300/CBP at nucleosome-occupied enhancers

Abstract: Pioneer transcription factors are defined by their ability to bind nucleosome-occupied regions. Here, we discuss the properties of nucleosomes bound by pioneers at enhancer regions. We describe how select pioneers bind nucleosome-occupied or -depleted enhancer sites. Importantly, by revisiting and expanding existing data sets, we show differential H2A.Z and p300/CBP association at bound enhancers, highlighting two possible pioneering modes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Recently, we have extended these observations also to developmental signaling pathways: H2A.Z localizes at Notch responsive enhancers where it plays a negative role with regards to the expression of Notch target genes [57]. Interestingly, it has been observed that pioneering factors-bound enhancers exist with two different H2A.Z distributions: a) H2A.Z localizes at the center of Ets1- and Oct4-bound enhancer sites, whereas b) it is enriched at nucleosomes flanking forkhead box protein A2 (FoxA2) or C/EBPα-bound enhancer sites [167]. Table 4 provides the complete list of enhancers, which are bound by signal-specific TFs and have been linked to H2A.Z-mediated regulation.…”
Section: H2az At Enhancers and Promotersmentioning
confidence: 99%
“…Recently, we have extended these observations also to developmental signaling pathways: H2A.Z localizes at Notch responsive enhancers where it plays a negative role with regards to the expression of Notch target genes [57]. Interestingly, it has been observed that pioneering factors-bound enhancers exist with two different H2A.Z distributions: a) H2A.Z localizes at the center of Ets1- and Oct4-bound enhancer sites, whereas b) it is enriched at nucleosomes flanking forkhead box protein A2 (FoxA2) or C/EBPα-bound enhancer sites [167]. Table 4 provides the complete list of enhancers, which are bound by signal-specific TFs and have been linked to H2A.Z-mediated regulation.…”
Section: H2az At Enhancers and Promotersmentioning
confidence: 99%
“…H2A.Z has been shown to destabilize nucleosomes and is often found at active promoters and enhancers (Martire and Banaszynski 2020), which we also observed in our C1 cluster. The role of H2A.Z in closed chromatin is less clear, but H2A.Z occupancy seems to correlate with pioneer TF binding to nucleosome-occupied regions and has been suggested to act as a scaffold for binding of pioneer TFs and chromatin remodelers (Cauchy, Koch, and Andrau 2017;Subramanian, Fields, and Boyer 2015). Whether SOX9 requires destabilized nucleosomes for chromatin opening and activation of target enhancers remains undetermined, but the requirement for H2A.Z enrichment and motif presence is evident from our study.…”
Section: Discussionmentioning
confidence: 57%
“…ChIP-seq analysis of OCT4 and SOX2 revealed that a large fraction of their binding sites (respectively 28.2% and 42%) was more occupied upon IAA treatment, in line with TOBIAS and chromatome analysis (Figure 5G and H). However, OCT4 was reported to bind H2A.Z nucleosomes 61 and to lose binding upon H2A.Z knockdown 5 . Accordingly, sites bound by OCT4 only lost binding upon H2A.Z swapping with H2A, in contrast to sites bound by both OCT4 and SOX2 (Figure S5F).…”
Section: Resultsmentioning
confidence: 99%